Survey of the Fishing Cat Prionailurus viverrinus Bennett, 1833 (Carnivora: Felidae) and some aspects impacting its conservation in India - S. Mukherjee (Journal of Threatened Taxa, 2012)
The Fishing Cat Prionailurus viverrinus is a medium sized cat that is widely but patchily distributed across Asia and strongly associated with wetlands. It is among the 15 felid species that inhabit India and like other smaller cat species it is very poorly understood. Apart from a few recent surveys in specific locations, no concerted effort has been made to assess its current distribution and threats to its persistence within India. In this study we collected scats from natural habitats, through six states including five protected areas throughout India and performed informal interviews with locals to get a better overview of the current distribution and threats for Fishing Cats in India. Of the 114 scats used for molecular analysis, 37% were assigned to felids, including 19 Fishing Cats. We confirmed that Fishing Cat populations persisted in all locations where they were recorded before, including Keoladeo Ghana, from where it was reported in recent years that fishing cats are possibly extinct. Most populations face imminent threats with the worst being in the Howrah District of West Bengal where 27 dead individuals were traced during the study period of only one year. The major threats across populations include ecologically unbalanced land policies and land uses, direct persecution due to human-Fishing Cat conflicts as well as ritual hunts. To address these threats we recommend a stronger dialogue among scientists, policy makers, administrators, locals and other stake holders such as commercial fish and prawn cultivators. Further awareness campaigns for stakeholders, and surveys for monitoring fishing cat populations, studying their ecology and estimating economic losses to local people due to the Fishing Cat predation on livestock and poultry, is needed in order to design effective conservation strategies.